Kualitas dan akses informasi di Perpustakaan Umum Daerah Kota Bogor - Encang Saepudin; Nur Indah Srirezeki; Khadijah, Ute Lies Siti (Innovative: Journal Of Social Science Research, 2025)
The quality of library services plays an important role in encouraging public interest in reading, especially among students. Although the interest in reading among Indonesian people continues to increase, the reading interest index is still relatively low when compared to other countries. This study aims to analyze the quality of services and access to information at the Bogor City Regional Public Library. The research method used is a quantitative approach with a descriptive design. The population in this study were students and students who used the Bogor City Public Library in the period April to June 2024, totaling 212 people. Data were obtained from 68 respondents using a simple random sampling technique through a questionnaire, supported by interviews, observations, and literature studies. Data analysis was carried out descriptively through the stages of data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that the quality of service and ease of access to information in the library can meet the information needs of users efficiently. The use of modern equipment and facilities that support independence in accessing information creates a conducive environment for learning and research activities, thus encouraging users to be more active in searching for and reading information in the library.